Influence of amount of pesticide and amount of PPE to diastolic blood pressure of farmers in Bumen Village, Sumowono District, Semarang Regency - Atka Kurnia Sari; Tri Joko; Nikie Astorina Yunita Dewanti (Public Health Faculty, Diponegoro University, Semarang, Indonesia, 2018)
Background: Farmers in Bumen Village used pesticide from group of organophospat, carbamate, piretroid, and nicotinoid. The dose of pesticide that mix in one tank is not appropriate dosage. A preliminary survey found that farmers mixed more than a two types of pesticides and 100% of farmers did not use the complete Personal Protective Equipment (PPE) when preparing pesticides to spray. Hypertension is more prevalent in males with an 18.8% prevalence in Sumowono District in 2015 and becomes the number one disease each month in 2017. The purpose of this study was to determine the influence of the amount of pesticide and the amount of PPE with diastolic blood pressure in farmers in Bumen Village, Sumowono District, Semarang Regency. Independent variables were amount of pesticide and amount of PPE. Dependent variable was diastolic blood pressure.Methods: This study was observational with cross sectional design using purposive sampling. Samples were 35 respondents. The measurement methods were questionnaire and digital tensimeter. Data analysis used Rank Spearman.Results: The results showed that measurement of diastolic blood pressure has an average of 88.75 mmHg. The amount of pesticide (p=0,007; r=0,455) had an influence with diastolic blood pressure, positive correlation, the strenght of correlation was enough and the amount of PPE (p=0,034; r=-0,36) had an influence with diastolic blood pressure, negative correlation, the strenght of correlation was enoughConclusions: From this study can be concluded that the amount of pesticide and the amount of PPE affected the diastolic blood pressure in farmers in Bumen Village, Sumowono District, Semarang Regency.